Consequences of platelet-educated cancer cells on the expression of inflammatory and metastatic glycoproteins - Mélanie Langiu; Lydie Crescence; Diane Mège; Christophe Dubois; Laurence Panicot-Dubois (PLoS ONE, 2025)
Cancer-associated thrombosis, a major cause of mortality in cancer patients, exhibits a 4 to 7 times higher incidence compared to the general population. Platelet activation by tumor cells contributes to this pro-thrombotic state. Cancer cell-educated platelets have also been described to be implicated in promoting metastasis. Intriguingly, our team, among others, unveils a reverse process, wherein platelets educate cancer cells by transferring lipids, RNAs, and proteins. Here, focusing on colorectal and pancreatic cancers, our study investigates genes and proteins mediating platelet education of cancer cells. We demonstrated, for the first time, that platelets can educate cancer cells by inducing changes in the transcription of genes related to glycosylation, inflammation, and metastasis in cancer cells themselves. These results indicate a direct impact of platelets on cancer cell phenotype. This novel insight suggests potential therapeutic avenues for cancer treatment, disrupting platelet-mediated alterations and influencing the course of cancer progression.